Surface Modified Arundo Donax Natural Fibers for Oil Spill Recovery. Issue 14 (28th October 2022) - Piperopoulos, Elpida; Khaskhoussi, Amani; Fiore, Vincenzo; Calabrese, Luigi
ABSTRACT: The use of green materials for oil recovery applications is the goal to be achieved to reduce the environmental impact of these essential processes. In this context, Arundo Donax L. is a plant known for its wide uses whose absorbent properties have been previously investigated. In this paper, the influence of silane surface treatment on the absorbent behavior of natural fibers extracted from the culms of this eco-friendly and cost-effective material was assessed. A close correspondence has been identified between the physical characteristics of the investigated oil and the fiber size, by means of microstructural and morphological analysis. Excellent results have been achieved with an absorption uptake of six to almost eight times its own weight, coupled with an improved selectivity of pollutant/water absorption, making the surface modified Arundo Donax fibers a potential effective material for oil recovery applications.